Decreased methylglyoxal-mediated protein glycation in the healthy aging mouse model of ectopic expression of UCP1 in skeletal muscle - Jinit, Masania (2023)
Mice with ectopic expression of uncoupling protein-1 (UCP1) in skeletal muscle exhibit a healthy aging phenotype with increased longevity and resistance to impaired metabolic health. This may be achieved by decreasing protein glycation by the reactive metabolite, methylglyoxal (MG). We investigated protein glycation and oxidative damage in skeletal muscle of mice with UCP1 expression under control of the human skeletal actin promoter (HSA-mUCP1) at age 12 weeks (young) and 70 weeks (aged). We found both young and aged HSA-mUCP1 mice had decreased advanced glycation endproducts (AGEs) formed from MG, lysine-derived Nε(1-carboxyethyl)lysine (CEL) and arginine-derived hydroimidazolone, MG-H1, whereas protein glycation by glucose forming Nε-fructosyl-lysine (FL) was increased ca. 2-fold, compared to wildtype controls. There were related increases in FL-linked AGEs, Nε-carboxymethyl-lysine (CML) and 3-deoxylglucosone-derived hydroimidazolone 3DG-H, and minor changes in protein oxidative and nitration adducts. In aged HSA-mUCP1 mice, urinary MG-derived AGEs/FL ratio was decreased ca. 60% whereas there was no change in CML/FL ratio – a marker of oxidative damage. This suggests that, normalized for glycemic status, aged HSA-mUCP1 mice had a lower flux of whole body MG-derived AGE exposure compared to wildtype controls. Proteomics analysis of skeletal muscle revealed a shift to increased heat shock proteins and mechanoprotection and repair in HSA-mUCP1 mice. Decreased MG-derived AGE protein content in skeletal muscle of aged HSA-mUCP1 mice is therefore likely produced by increased proteolysis of MG-modified proteins and increased proteostasis surveillance of the skeletal muscle proteome. From this and previous transcriptomic studies, signaling involved in enhanced removal of MG-modified protein is likely increased HSPB1-directed HUWE1 ubiquitination through eIF2α-mediated, ATF5-induced increased expression of HSPB1. Decreased whole body exposure to MG-derived AGEs may be linked to increased weight specific physical activity of HSA-mUCP1 mice. Decreased formation and increased clearance of MG-derived AGEs may be associated with healthy aging in the HSA-mUCP1 mouse.